2019
DOI: 10.1111/cpr.12630
|View full text |Cite
|
Sign up to set email alerts
|

miR‐92b promotes gastric cancer growth by activating the DAB2IP‐mediated PI3K/AKT signalling pathway

Abstract: Gastric cancer (GC) is currently the most common malignancy of the gastrointestinal tract, with a high mortality rate that ranks as the second most diagnosed cause of cancer-related death worldwide. 1 According to recent statistics, approximately one million newly diagnosed cases of GC are reported annually, and in 2013, the number of GC-related deaths was nearly 723 000. 2,3 Surgical resection remains the primary treatment for GC patients and can provide the best chance of cure, and chemotherapy and radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…To understand the underlying mechanisms of DAB2IP in this event, we explored possible downstream signaling pathways such as AKT and ERK, which are both closely associated with cancer cell proliferation and chemoresistance. [25][26][27] In line with previous studies, [20][21][22] we further confirmed the inhibitory effect of DAB2IP on AKT and ERK signaling pathway. We found that DAB2IP depletion notably increased the levels of phosphorylated AKT (p-AKT) and phosphorylated ERK (p-ERK) in both AGS and SGC7901 cells, but not their total protein levels ( Figure 5A).…”
Section: Dab2ip Regulates Akt and Erk Signaling Pathway In Gc Cellssupporting
confidence: 91%
See 2 more Smart Citations
“…To understand the underlying mechanisms of DAB2IP in this event, we explored possible downstream signaling pathways such as AKT and ERK, which are both closely associated with cancer cell proliferation and chemoresistance. [25][26][27] In line with previous studies, [20][21][22] we further confirmed the inhibitory effect of DAB2IP on AKT and ERK signaling pathway. We found that DAB2IP depletion notably increased the levels of phosphorylated AKT (p-AKT) and phosphorylated ERK (p-ERK) in both AGS and SGC7901 cells, but not their total protein levels ( Figure 5A).…”
Section: Dab2ip Regulates Akt and Erk Signaling Pathway In Gc Cellssupporting
confidence: 91%
“…7,[11][12][13][14][15][16] Recent studies [17][18][19] in prostate, bladder and renal cancer demonstrated that DAB2IP loss decreased cell sensitivity to chemotherapeutic agents or targeted drugs, suggesting a role for DAB2IP in chemoresistance in multiple cancer types. In consistency, previous studies [20][21][22] also showed that DAB2IP was significantly downregulated in GC tissues and DAB2IP knockdown promoted GC cell proliferation, migration as well as activation of the protein kinase B (AKT) and extracellular signal-regulated kinase (ERK) signaling pathways. However, the prognostic value and potential role of DAB2IP in GC cell sensitivity to chemotherapy have not been elucidated.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Ni et al found that miR-92b played a supporting role by targeting DOC-2/DAB2 interacting protein in GC cell proliferation. [ 28 ] Wang et al [ 29 ] showed that the up-regulation of miR-664a-3p remarkably enhanced the proliferation and invasion via the Hippo pathway in vitro and in vivo . MiR-192 and miR-215 target adenomatous polyposis coli, which is a well-known negative regulator of Wnt signaling function during the tumorigenesis of colorectal cancer to play an oncogenic in GC proliferation and migration.…”
Section: Proliferationmentioning
confidence: 99%
“…A similar regulatory loop has been described in hepatocellular carcinoma, where DAB2IP mRNA and protein levels were upregulated upon overexpression of circ-5692, able to sponge the DAB2IP-targeting miR-328-5p [ 90 ]. Several miRNAs of the miR-92a family were reported to target DAB2IP in multiple tumors [ 86 , 91 , 92 , 93 ]. DAB2IP inhibition by miR-556 in bladder and esophageal cancer fosters cells proliferation and sustains tumor progression via aberrant Ras-MAPK signaling activation [ 94 , 95 ].…”
Section: Post-transcriptional Inhibition Of Rasgaps In Cancermentioning
confidence: 99%